Identifying potential dietary treatments for inherited metabolic disorders using Drosophila nutrigenomics - Felipe Martelli; Jiayi Lin; Sarah Mele; Wendy Imlach; Oguz Kanca; Christopher K. Barlow; Jefferson Paril; Ralf B. Schittenhelm; John Christodoulou; Hugo J. Bellen; Matthew D.W. Piper; Travis K. Johnson (Cell Reports, 2024)
Summary: Inherited metabolic disorders are a group of genetic conditions that can cause severe neurological impairment and child mortality. Uniquely, these disorders respond to dietary treatment; however, this option remains largely unexplored because of low disorder prevalence and the lack of a suitable paradigm for testing diets. Here, we screened 35 Drosophila amino acid disorder models for disease-diet interactions and found 26 with diet-altered development and/or survival. Using a targeted multi-nutrient array, we examine the interaction in a model of isolated sulfite oxidase deficiency, an infant-lethal disorder. We show that dietary cysteine depletion normalizes their metabolic profile and rescues development, neurophysiology, behavior, and lifelong fly survival, thus providing a basis for further study into the pathogenic mechanisms involved in this disorder. Our work highlights the diet-sensitive nature of metabolic disorders and establishes Drosophila as a valuable tool for nutrigenomic studies for informing potential dietary therapies.